Light influences the effect of exogenous ethylene on the phenolic composition of Cabernet Sauvignon grapes - Liu, Meiying; Zhu, Qinggang; Yang, Yanhong; Jiang, Qianqian; Cao, Hui; Zhang, Zhenwen (Frontiers in Plant Science, 2024)
The gaseous phytohormone ethylene (ETH) plays a key role in plant growth and development, and is a major regulator of phenolic biosynthesis. Light has long been known to influence phytohormone signaling transduction. However, whether light influences the effect of ETH on the phenolic composition of grapes (Vitis vinifera L) is an open question. Here, the accumulation and composition of anthocyanins and non-anthocyanin phenolics were analyzed in Cabernet Sauvignon grapes under four treatments: light exposure with and without ETH treatment, and box-shading with and without ETH treatment. Both light and ETH promoted ripening, decreased the color index (L*, C*, and h*), and accelerated the color change from green to red and purplish red. Sunlight-exposed grapes had the highest contents of most anthocyanins, flavonols, flavan-3-ols, and hydroxybenzoic acids. In addition, light exposure increased the ratios of 3'5'-substituted/3'-substituted anthocyanins and flavonols, but decreased the ratios of methoxylated/non-methoxylated and acylated/non-acylated anthocyanins and flavan-3-ols. Notably, the effects of ETH were influenced by light exposure. Specifically, ETH treatment promoted anthocyanin and non-anthocyanin biosynthesis in light-exposed grapes, and their increasing multiples were remarkably higher under light-exposed conditions. Furthermore, ETH treatment decreased the ratios of methoxylated/non-methoxylated, 3'5'-substituted/3'-substituted, and acylated/non-acylated anthocyanins and flavan-3-ols in light-exposed grapes, each of which was 2 increased by ETH treatment in shaded grapes. Fifteen differential phenolic components were identified through partial least-squares-discriminant analysis (PLS-DA). Among them, cyanidin-3-O-(cis-6-O-coumaryl)-glucoside, petunidin-3-O-(6-O-acetyl)-glucoside, petunidin-3-O-(trans-6-O-coumaryl)-glucoside, petunidin-3-O-glucoside, myricetin-3-O-galactoside, kaempferol-3-O-galactoside, and kaempferol-3-O-glucoside were the main differential components between ETH treatments under different light conditions.